Contactless Conductivity Detection for Capillary Electrophoresis—Developments From 2020 to 2024 - Hauser, Peter C.; Kubáň, Pavel (Electrophoresis, 2024)
The review covering the development of capillary electrophoresis with capacitively coupled contactless conductivity detection from 2020 to 2024 is the latest in a series going back to 2004. The article considers applications employing conventional capillaries and planar lab‐on‐chip devices as well as fundamental and technical developments of the detector and complete electrophoresis instrumentation.